MyNeutronDAQ: A general program for data acquisition of neutron scattering spectrometers at China Mianyang Research Reactor and on‐line data‐analysis. (3rd November 2020) - Wang, Tingting; Pang, Beibei; Li, Xinxi; Wang, Yan; Huang, Chaoqiang; Gong, Jian; Sun, Guangai; Liu, Dong
Abstract: MyNeutronDAQ, a graphical user interface (GUI) program for data acquisition of neutron scattering spectrometers at China Mianyang Research Reactor (CMRR) and on‐line data‐analysis has been developed. The program is written in Microsoft Visual C++, which runs under Windows operating systems. Based on the characters of the hardware connection and time‐to‐digital converter (TDC) systems of the spectrometers (taking the time‐of‐flight and polarized neutron reflectometer [TPNR] Diting as the example), a valid event identification and screening protocol is embedded into the program. Moreover, the program design and key features of MyNeutronDAQ such as visualization interface, optional output data format, batch mode, and functions of user‐friendly on‐line analysis, are presented. Taking the program specifically for small‐angle neutron scattering (SANS) Suanni as the example, specific applications of the MyNeutronDAQ are further presented.